Analisis Penerapan Sasaran Keselamatan Pasien di Instalasi Gawat Darurat Rumah Sakit X Provinsi Sulawesi Utara - Astryd Sendoh; Junita M. Pertiwi; Jeanette I. Ch. Manoppo (Universitas Sam Ratulangi, 2023)
Abstract: Patient safety is the cornerstone of health service quality and a top priority in providing health services worldwide. This study was aimed to obtain an overview of the implementation of patient safety goals at the Emergency Department of X Hospital, North Sulawesi Province. This was a qualitative study carried out at the Emergency Department of X Hospital, North Sulawesi Province from November 2022 to January 2023. The research instruments were the researchers themselves (human instruments). The results showed that the understanding of health workers about patient safety goals (SKP 1-3, 5, 6) at the Emergency Department of X Hospital and the availability of facilities and infrastructure supporting its implementation were in accordance with hospital accreditation standards of the Ministry of Health of the Republic of Indonesia 2022 but they were not optimal, therefore, the implementation of patient safety goals was also not optimal. Moreover, the related facilities and infrastructure of SKP 4 were not yet optimal. In conclusion, the patient safety goals at the Emergency Department of X Hospital North Sulawesi Province have been implemented in accordance with the hospital accreditation standards of the Ministry of Health of the Republic of Indonesia 2022 but are not optimal due to the obstacles in health workers’ compliance. The related facilities and infrastructure are not yet optimal since the new hospital has just begun to operate. Keywords: patient safety goals; health workers; Emergency Department Abstrak: Keselamatan pasien merupakan landasan kualitas pelayanan kesehatan dan prioritas utama dalam memberikan pelayanan kesehatan di seluruh dunia. Penelitian ini bertujuan untuk memberikan gambaran penerapan sasaran keselamatan pasien di Instalasi Gawat Darurat (IGD) RS X Provinsi Sulawesi Utara. Jenis penelitian ialah kualitatif yang dilakukan di IGD RS X Provinsi Sulawesi Utara pada bulan November 2022-Januari 2023. Instrumen penelitian yang digunakan ialah peneliti sendiri (human instrument). Hasil penelitian mendapatkan bahwa pemahaman tenaga kesehatan mengenai Sasaran Keselamatan Pasien (SKP 1–3, 5, 6) di IGD RS X Provinsi Sulawesi serta ketersediaan sarana dan prasarana yang mendukung pelaksanaannya sudah sesuai dengan standar akreditasi Rumah Sakit Kementerian Kesehatan RI tahun 2022 tetapi belum optimal sehingga penerapan SKP belum optimal. Sarana dan prasarana pendukung pelaksanaan SKP 4 di IGD masih dalam pemenuhan sesuai standar yang ditetapkan. Simpulan penelitian ini ialah sasaran keselamatan pasien di IGD RS X Provinsi Sulawesi Utara sudah diterapkan sesuai standar akreditasi rumah sakit Kementerian Kesehatan RI 2022 tetapi belum optimal karena adanya kendala pada kepatuhan petugas. Sarana dan prasarana terkait belum optimal dan masih dalam proses melengkapi karena rumah sakit baru beroperasi. Kata kunci: sasaran keselamatan pasien; petugas kesehatan; Instalasi Gawat Darurat